Mesenchymal Stem Cells Isolated from Adipose and Other Tissues: Basic Biological Properties and Clinical Applications - Hakan Orbay; Morikuni Tobita; Hiroshi Mizuno (Stem Cells International)
Mesenchymal stem cells (MSCs) are adult stem cells that were initially isolated from bone marrow. However, subsequent research has shown that other adult tissues also contain MSCs. MSCs originate from mesenchyme, which is embryonic tissue derived from the mesoderm. These cells actively proliferate, giving rise to new cells in some tissues, but remain quiescent in others. MSCs are capable of differentiating into multiple cell types including adipocytes, chondrocytes, osteocytes, and cardiomyocytes. Isolation and induction of these cells could provide a new therapeutic tool for replacing damaged or lost adult tissues. However, the biological properties and use of stem cells in a clinical setting must be well established before significant clinical benefits are obtained. This paper summarizes data on the biological properties of MSCs and discusses current and potential clinical applications.